Analysis of the interaction between personality dysfunction and traits in the statistical prediction of physical aggression: Results from outpatient and community samples. (21st June 2021) - Leclerc, Philippe; Savard, Claudia; Vachon, David D.; Faucher, Jonathan; Payant, Maude; Lampron, Mireille; Tremblay, Marc; Gamache, Dominick
Abstract: The Alternative Model for Personality Disorders (AMPD), included in the Diagnostic and Statistical Manual of Mental Disorders (5th ed.) and the World Health Organization's International Classification of Diseases (11th ed.; ICD‐11) are, respectively, hybrid categorical‐dimensional and dimensional frameworks for personality disorders (PDs). Both models emphasize personality dysfunction and personality traits. Previous studies investigating the links between the AMPD and ICD‐11, and self‐reported physical aggression have mostly focused on traits and did not take into account the potential interaction between personality dysfunction and traits. Thus, the aim of this study is to identify dysfunction*trait interactions using regression‐based analysis. Outpatients with personality disorder from a specialized public clinic ( N  = 285) and community participants ( N  = 995) were recruited to complete self‐report questionnaires. Some small‐size, albeit significant and clinically/conceptually meaningful personality dysfunction*trait interactions were found to predict physical aggression in both samples. Interaction analyses might further inform, to some degree, about the current discussion pertaining to the potential redundancy between dysfunction and traits, the optimal personality dysfunction structure (in the case of the AMPD), as well as clinical assessment based on AMPD/ICD‐11 PD frameworks.